Improving strawberry shelf life using chitosan and zinc oxide nanoparticles from ginger-garlic extracts - Ayesha Sani; Dilawar Hassan; Muhammad Ehsan; Elvia Patricia Sánchez-Rodríguez; Dulce Viridiana Melo-Máximo (Applied Food Research)
To mitigate spoilage in strawberries, we developed coating formulations composed of chitosan (CH) and zinc oxide nanoparticles (ZnO NPs), enhanced with ginger and garlic extracts. Treated samples of commercial strawberries were exposed to different formulations: 1 % CH, and 1 % ZnO NPs, 2 % ZnO NPs, 3 % ZnO NPs in combination with 1 % CH. Samples were stored under refrigeration at 4 °C and ambient conditions at 27 °C, with untreated strawberries as the control group. Quality indices evaluated included weight loss, pH, firmness, antioxidant activity, ascorbic acid content, total soluble solids, total reducing sugars, titratable acidity, and percentage infection during storage. The results showed that CH and ZnO NPs (sized 40.46 nm) significantly improved all measured parameters, enhancing strawberry preservation for up to 30 days. Applying ZnO NPs with CH reduced weight loss and decay rate by about 40 %. The SEM images showed that the CH coatings were quite visible on the surface. Further, FTIR spectra also confirmed the presence of ZnO NPs. CH-ZnO NPs coatings appear promising for extending strawberries' shelf life and preserving quality and nutritional value during storage and transportation.